Metal tolerance and biosorption capacities of bacterial strains isolated from an urban watershed - Pagnucco, Grace; Overfield, Dustin; Chamlee, Yanesa; Shuler, Claudia; Kassem, Amin; Opara, Somie; Najaf, Hawraa; Abbas, Lana; Coutinho, Oliver; Fortuna, Aleksa; Sulaiman, Fatima; Farinas, James; et al. (Frontiers in Microbiology, 2023)
Rapid industrialization and urbanization have led to widespread metal contamination in aquatic ecosystems. This study explores the metal tolerance and biosorption characteristics of four bacterial strains (Serratia sp. L2, Raoultella sp. L30, Klebsiella sp. R3, and Klebsiella sp. R19) isolated from Saint Clair River sediments. These strains effectively removed various metal cations (As 3+ , Pb 2+ , Cu 2+ , Mn 2+ , Zn 2+ , Cd 2+ , Cr 6+ and Ni 2+ ) in single and multi-metal solutions.Minimum inhibitory concentration (MIC) assays revealed strain-specific variations in metal tolerance, with L2 and L30 exhibiting higher tolerance. Surprisingly, R3 and R19, despite lower tolerance, demonstrated superior metal removal efficiency, challenging the notion that tolerance dictates removal efficacy. In single-metal solutions, R3 and R19 excelled at extracting various metal ions, while competitive binding in multi-metal solutions hindered removal. However, R3 and R19 retained higher removal efficiencies, possibly due to enhanced flocculation activities facilitating metal-ion contact. Comprehensive Fourier-transform infrared (FTIR) analysis highlighted the strains' metal-binding capabilities, with novel peaks emerging after metal exposure, indicative of extracellular polymeric substance (EPS) production. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) confirmed metal accumulation on bacterial surfaces and within cytoplasmic regions and revealed morphological changes and metal adsorption patterns, emphasizing the strains' ability to adapt to metal stress.Scanning transmission microscopy (STEM) and EDX analysis uncovered metal accumulation within bacterial cells, underscoring the complexity of microbial-metal interactions. This study also confirms that the simultaneous presence of an aqueous solution may cause a mutual inhibition in the adsorption of each metal to the EPS resulting in reduced metal uptake, which emphasizes the need to select specific bacterial strains for a given metal-containing effluent.The differences in metal distribution patterns between Klebsiella sp. R19 and Raoultella sp. L30 suggest species-specific metal accumulation strategies driven by environmental conditions and metal availability. The heavy metal-removing capabilities and the ability to grow over a wide range of metal concentrations of the strains used in this study may offer an advantage to employ these organisms for metal remediation in bioreactors or in situ.